Molecular Characterization of Two Toll Receptors in Hyriopsis cumingii and Their Potential Roles in Antibacterial Response - Huang, Ying; Zhang, Guosong; Ren, Qian (Frontiers in Physiology, 2019)
Tolls/Toll-like receptors (TLRs) play a key role in innate immunity by detecting the invading microbes and subsequently activating downstream signaling cascades. In this study, two new molluscan Toll members (designed as HcToll6 and HcToll7) were identified from triangle-shell pearl mussel (Hyriopsis cumingii). The obtained HcToll6 full-length cDNA was 3207 bp consisting of a 2223 bp open reading frame (ORF) that encoded a peptide of 740 amino acids. HcToll7 cDNA is a 3216 bp molecule that contains an ORF of 2139 bp encoding a protein of 712 amino acids. The deduced HcToll6 and HcToll7 proteins share two common structures: extracellular leucine-rich repeat (LRR) domains and intracellular Toll/interleukin-1 receptor (TIR) domain. Quantitative real-time PCR results showed that HcToll6 and HcToll7 were mainly expressed in the hepatopancreas and the gills, and they responded rapidly to bacterial stimulation. RNA interference by dsRNA results revealed that HcToll6 and HcToll7 RNAi strongly decreased the expression of lysozyme (HcLyso) and defensin (HcDef) in the gills of RNAi-treated mussels with Vibrio parahaemolyticus challenge. As a pattern recognition receptor, the prokaryotic expressed the recombinant LRR domains of HcToll6 and HcToll7 (rHcToll6-LRR and rHcToll7-LRR) could bind to Gram-positive and Gram-negative bacteria and had a strong tendency to recognize lipopolysaccharide (LPS) and peptidoglycan (PNG). rHcToll6-LRR and rHcToll7-LRR exhibited a significant in vitro bactericidal activity against V. parahaemolyticus and Staphylococcus aureus. These findings provide useful information to characterize Tolls in mussels.